Analisis Peran Sektor Pertanian dalam Meningkatkan Pertumbuhan Ekonomi Regional Kecamatan Kupang Barat - Fikran Sonya Bangkole; Marthen R. Pellokila; Nikson Tameno (Universitas Veteran Bangun Nusantara, 2024)
This research aims to analyze the important role andfunctional role of the agricultural sector in economic growth in West Kupang District. In the current development toface the economic dynamics that exist in West Kupang District. Agriculture is one of the sectors carried out by the people of West Kupang and District to meet economic needs. On average, the people of West Kupang District manage natural resources to advance the important role of agriculture in meeting thefood and clthing andshelter needs of the people of West Kupang and its surroundings. Because agriculture is one of the biggest centersfor advancing the economic structure of West Kupang District, if seenfrom the formation of the GRDP of West KupangRegency, the agricultural sector alsoplays arole in terms of labor absorption. Because of the abundant natural resources andfertile land.